2022
DOI: 10.1002/ctpp.202100220
|View full text |Cite
|
Sign up to set email alerts
|

Wave breaking limit in arbitrary mass ratio warm plasmas

Abstract: The maximum sustainable amplitude, so‐called wave breaking limit, of a nonlinear plasma wave in arbitrary mass ratio warm plasmas is obtained in the non‐relativistic regime. Using the method of Sagdeev potential, a general wave breaking formula is derived by taking into account the dynamics of both the species having finite temperature. It is found that the maximum amplitude of the plasma wave decreases monotonically with the increase in temperature β−$$ {\beta}_{-} $$ of the negative species (temperature β+$$… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…The potential for such a single-temperature EP plasma is guaranteed to be symmetric about f = 0 as the constituents have equal mass and temperature as seen in figure 3 (curve 1). This is in agreement with the results reported for the cold equal mass plasma case in [18]. It is interesting to note that this symmetry is maintained even for non-zero values of α and β h , i.e.…”
Section: Derivation Of Wave-breaking Limitsupporting
confidence: 92%
See 2 more Smart Citations
“…The potential for such a single-temperature EP plasma is guaranteed to be symmetric about f = 0 as the constituents have equal mass and temperature as seen in figure 3 (curve 1). This is in agreement with the results reported for the cold equal mass plasma case in [18]. It is interesting to note that this symmetry is maintained even for non-zero values of α and β h , i.e.…”
Section: Derivation Of Wave-breaking Limitsupporting
confidence: 92%
“…Thus, the fictitious particle will execute one-dimensional oscillations inside this potential well. In general, the Sagdeev potential is not symmetric owing to differences in masses and temperatures of the various constituents of the plasma [16][17][18][19]. But for our case of a two-temperature EP plasma, it is easily verifiable that the Sagdeev potential U(f) given by equation (24) is indeed symmetric about f = 0 (see curve 2 in figure 3).…”
Section: Derivation Of Wave-breaking Limitmentioning
confidence: 76%
See 1 more Smart Citation
“…Nonlinear wave dynamics and its breaking phenomena in usual electron-ion plasmas have been a topic of fundamental interest [22][23][24][25][26][27][28][29]. Nevertheless, a very few theoretical studies can be found in the existing literature on the high frequency wave phenomena in classical dusty plasmas [30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%